PENGEMBANGAN MEDIA PEMBELAJARAN SINAU AKSAWA UNTUK PEMBELAJARAN BAHASA JAWA SEKOLAH DASAR - Riska Hilda Novela; Sripit Widiastuti; Desy Anindia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Based on the results of observations in classes III, IV, V and VI of elementary schools, it can be concluded that students have difficulty understanding Javanese language learning using Javanese script material because the learning media used is less interesting. Furthermore, to solve the problems that occur, new innovations should be created that are tailored to the needs of students so that there are no obstacles in the Javanese language learning process, especially in Javanese script material. The aim of this research is to produce Sinau Aksawa products for students in grades III, IV, V and VI of elementary school as a learning medium. This research is development research. The research and development model used is ADDIE. Based on the results of research and development of learning media products, Sinau Aksawa received a score of 90.47% from media validators, 92.67% from material and language validators. Apart from that, the readability test results show that the Sinau Aksawa learning media received a score of 95% from teachers and a score of 82.55% from students.